Analisis Kasus Begal Sepeda Motor di Kota Kendari (Studi Kasus Putusan Nomor.308/Pid.B/2021/PN Kdi) - Widodo, Karina Luana Pramesti; Faridah, Hana (Jurnal Panorama Hukum, 2021)
During the COVID-19 Pandemic, criminal acts of crime increased in big cities. The rise of the crime of theft of motorbikes is a social problem, namely problems in the community, because the perpetrators and victims are members of the community as well. In the perspective of criminology, crime is a human act that tarnishes the basic values and norms of society, acts that violate the rules that live and develop in society. Eventhough crimes are criminal acts and the sanctions or punishments, the community still commits crimes. The method used in this study is a normative legal research method, research that examines documents, various secondary data such as legislation, legal theory, court decisions and legal expert opinions. Several factors cause people to commit crimes of theft and violence because of the necessities of life. However, it is a bad act that must be done because it endangers other people to the point of taking lives.